International monetary problems, 1957-1963 : selected speeches of Per Jacobsson - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1964)
Selected speeches of Per Jacobsson
"Articles and books, by Mr. Jacobsson 1957-1963": p. 347-355.
Includes bibliographical references and index.
rua 19/04/2017; usc 13/04/2018
Loans
Keywords: Jacobsson, Per; International Monetary Fund; Foreign exchange